Analisis Pengaruh Motivasi, Kompensasi, dan Pengembangan SDM Terhadap Kinerja Anak Buah Kapal Deck Departement Melalui Variabel Intervening Kepuasan Kerja - Renny Hermawati; Suganjar Suganjar (Majalah Ilmiah Bahari Jogja, 2020)
The results of an internal audit conducted at PT Halmahera found a phenomenon that there was a decline in the performance of the Deck Departement Ships crew on every vessel owned by the company during 2017 to 2019. It was obtained that there was a decrease in the number of Deck Departement ships crew in the company which has a Good and Very Good performance assessment. As for the Departments of the Crew Crew Departments with performance ratings Fair, Poor and Very Poor have increased. This makes an indication that there are performance issues at PT Halmahera which then become a reference for conducting research on the performance of the Departments of the Crew Crew. To be able to answer the performance problems that occur in the company, it is done by using a variable approach to motivation, compensation, human resource development, performance, and using job satisfaction as an intervening variable. Various data used in this study were obtained through interviews. The interview was conducted using a questionnaire given to 115 respondents of the Departments of the Crew Crew at PT Halmahera. Furthermore, the data is used to test the model and to analyze the influence of the above variables with the Structural Equation Modeling (SEM) approach with the AMOS program. After testing, the results obtained indicate that motivation, compensation and HR development, statistically proven to have a significant positive effect on job satisfaction, while those proven to have a significant positive effect on performance are only the development of HR and motivation, the effect of compensation, on performance, cannot be proven in this study.